Adverse effects of electronic cigarette vapor condensation on oral cells: A scoping review (Revista Contexto & Saúde, 2026)
Electronic cigarettes (ECs), when internally heated, generate aerosol through e-liquid, with part of it being absorbed into the bloodstream. Consequently, little is known about the potential adverse events of this vapor on oral cells, which may contribute to alterations in their functionality. The present study aims to organize data from the literature on the adverse effects of EC vapor condensation on oral cavity cells. The analysis was conducted following the methodological approach of PRISMA-ScR and the Joanna Briggs Institute (JBI). Thus, two researchers from the team independently searched the PubMed/MEDLINE, Scopus, Web Of Science, and LILACS databases using combinations of descriptors through "and/or," tabulating studies published in English over a 10-year period (January 1, 2013, to October 13, 2023), with the assistance of the EndNote reference manager. With the search, a total of 803 studies were located, of which 15 in vitro studies were included in the final analysis. Among the qualitative results, exposure to EC vapor for up to 72 hours caused damage to deoxyribonucleic acid (DNA), oxidative stress, double-strand DNA breaks, apoptosis, cytotoxicity, and genotoxicity in human gingival fibroblasts (FGH), gingival mesenchymal stem cells (CTMG), primary human gingival epithelial cells (CEGHP), normal human oral keratinocytes (QOHN), and clustered human gingival epithelial progenitors (HGEPp). The evaluated cell cultures also showed a high percentage of apoptotic cells positive for terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL), delaying their migration. Thus, xenobiotic metabolism, oxidative stress response, and processes related to inflammation are influenced by EC vapor in oral cells.
Keywords: Cigarro electronico; Forma celular; Citotoxicidad inmune; Factor de inducción de apoptosis